SOME ASPECTS OF THE BIOLOGY OF TACHYSURUS TENUISPINIS DAY FROM VERAVAL - Raje, Sadashiv Gopal (Journal of Indian Fisheries Association, 2015)
The regression coefficients in length-weight relationship of males andfemales of Tachysurus tenuispinis differ significantly. The relative conditionfactor was calculated for females in relation to various lengths and months.The sex ratio in the catch varied widely in the different months. The numberof eggs ranged from 72 to 89 for the fish of length 394 to 570 mm. Emptystomachs occurred in a very high percentage (63.5%) of the total stomachsexamined. This is a bottom carnivorous feeder. The main food items foundin the guts in order of preference were crustaceans, polychaetes, molluscs,fishes and echinoderms.Keywords: Tachysurus tenuispinis, length-weight relationship, relativecondition factor, sex ratio, fecundity, food and feeding habit